PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI SARANA MEDIA PROMOSI BUDIDAYA TANAMAN HIAS BAPAK SUNYOTO DI PEKON AMBARAWA (LP3K Lampung, 2021)
Globalization is a challenge for Small and Medium Enterprises (UKM) to survive. Information technology, especially social media, offers benefits for SMEs to increase their marketing. This research was conducted to identify the use of social media and its benefits in Tanaman Hias Bapak Sunyoto Pekon Ambarawa UKM. The results showed that the most widely used social media was Facebook. Social media is used by most SMEs to make personal contact with consumers, promote or advertise, record consumer needs and convey responses to consumers. Social media is an effective communication medium for SMEs, can increase market share, and assist business decisions. The use of social media can increase sales volume by more than 100% if it is done consistently and updated information every day. The conclusion of this study, social media has the potential to increase market share and sales volume, so it needs to be used optimally and consistently.